Perempuan dalam Pusaran Prostitusi: Kajian Yuridis Normatif dalam Fenomena Prostitusi Online di Indonesia - Khasanah, Uswatun (IAIN Pekalongan, 2019)
This paper examines prostitution which in practice has always been identified with women. Prostitution is a social problem that is passed down from time to time with various modes that always develop along with the development of lifestyle and technology. The focus of this study is how is the normative juridical review of the issue of women and prostitution? The method used in this article is the library study method. Through a normative juridical approach, the author will examine the issue of prostitution based on the main legal material, namely to see the arguments originating from the Qur'an and hadith, as well as legislation in force in Indonesia. In the final section the author tries to present a solution to stem the practice of prostitution. In this study it was found that prostitution in Indonesia has existed since the kingdom era, continued during the Dutch and Japanese colonies. Prostitution is a crime that is contrary to Islamic law and legislation in Indonesia. Surat an-Nur (24): 30-33 strictly prohibits the practice of prostitution. This ban applies to anyone not only to women who are prostitutes. Juridically normative legislation in Indonesia concerning prostitution is article 296, 506 of the KUHP, UU No. 11 of 2008 concerning Information and Electronic Transactions, UU No. 44 of 2008 concerning Pornography, UU No. 21 of 2007 concerning Eradication of Criminal Acts on Trafficking in Persons and UU No. 23 of 2003 concerning Child Protection. Efforts to stem the main prostitution began with the family. Optimizing the role of parents -both father, mother and teacher as an extension of their parents' hand- can be a solution in an effort to improve children's moral resilience, which in turn can stem a variety of negative behaviors that conflict with norms and religion, including prostitution.